PKM Literasi Gizi melalui Gerakan Sadar Gula pada makanan dan Minuman Kemasan untuk Siswa Sekolah Dasar - Kadir, Iftitah Rahmi; Alti, Rahmi Mudia; Agustianti, Rifka (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Elementary school children frequently consume packaged foods and drinks, often unaware of their high sugar content. This PKM activity aimed to enhance students' nutritional literacy through lectures and interactive discussions. Pre-test and post-test evaluations were conducted to measure knowledge improvement. Before the intervention, only 30% of students understood nutritional labels, increasing to 80% afterward. The ability to recognize sugar-related terms rose from 25% to 85%, and awareness of daily sugar intake limits improved from 20% to 90%. These results indicate that educational programs using lectures and hands-on learning effectively increase children's nutritional awareness and promote healthier consumption habits.